Pengaruh Moralitas Individu, Asimetri Informasi, Efektivitas Pengendalian Internal dan Budaya Organisasi Terhadap Kecendrungan Kecurangan Akuntansi Pada LPD di Kabupaten Buleleng - Pujayani, Putu Eva Indah; Dewi, Putu Eka Dianita Marvilianti (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the variables of individual morality, information asymmetry, effectiveness of internal controls, and organizational culture on the tendency of accounting fraud. The research method used in this research is quantitative research methods with primary data obtained from questionnaire data which is measured using a Likert scale. This research was conducted at Village Credit Institutions in Buleleng Regency. The population in this study were all LPDs throughout Buleleng Regency, amounting to 169 LPDs. The sampling method was carried out by purposive sampling and obtained a total sample of 80 respondents. The data were analyzed using several analyzes including descriptive statistics, classical assumption tests and multiple regression analysis with the presentation of data assisted by the SPSS 20 program. The results of this study indicate that the variables of individual morality (X1), effectiveness of internal control (X3), organizational culture (X4) have negative and significant influence on the tendency of accounting fraud (Y). Meanwhile, the information asymmetry variable (X2) has a positive and significant effect on the tendency of accounting fraud (Y).Â